What does a dollar mean to you? utilizing intrinsic rewards within contingency management - Shirazi, Anaheed; Carley, Joseph A.; Ghahremani, Dara G.; Brody, Arthur L.; Lang, Ariel J. (Frontiers in Psychiatry, 2025)
Substance Use Disorders (SUDs) pose a significant public health challenge. Medications used for treatment of SUDs are limited in their efficacy, particularly in cannabis and stimulant use disorders, and non-pharmacological interventions have shown, at most, moderate effectiveness, leaving a continuing need for improved treatments. Contingency management (CM) is an evidence-based treatment with promising results, operationalized in SUD treatment programs by using monetary rewards to help patients achieve target behaviors such as abstinence. Several factors limit the viability of CM as a sustainable, effective treatment, suggesting insufficiency of monetary reinforcement alone. Implementation can be costly, requiring increased monetary reinforcers over time to reach target behaviors, and effects do not endure. We propose an integrative model of CM that explicitly incorporates intrinsic rewards into CM to enhance its effectiveness. This model involves redirecting salience attribution of monetary rewards towards goals and activities that are personally relevant and motivating for the individual that do not involve substance use. This integrative model of CM may address current challenges of and some of the barriers to implementation of CM in clinical practice.